Personal Marketing: A Strategy for Marketing Programs to Diverse Audiences - Lisa A. Guion; David C. Diehl (EDIS, 2010)
Revised! This document is FCS9222, one of a series by Lisa A. Guion and David C. Diehl that includes articles on planning programs to effectively reach diverse audiences. Published by the Family, Youth and Community Sciences Department, June 2010.